Usability of a mobile phone application to enhance activities of daily living in occupational therapy services for breast cancer survivors - Dulce Romero-Ayuso; Raquel García-López; Carmen Lozano-Villena; José R Martínez; Paula Parga-Amado; Paula García-Ferreiro; José A Gallud; María Lozano; José-Matías T (SAGE Publishing, 2023)
Background/Objective: The use of new technologies in rehabilitation to evaluate and improve occupational performance and quality of life is increasing. Technological applications in the health field could help meet the needs of patients, including those of women breast cancer survivors. The main aim of this study was to design a mobile phone application "MAIA" focused on the perceived needs of women who have had breast cancer to achieve optimal performance in their daily lives in a meaningful way. Methods: A cross-sectional usability study using an online questionnaire was designed. Sociodemographic and occupational performance data were collected. System Usability Scale, Engagement in Meaningful Activities Survey, Occupational Balance Questionnaire, General Self-Efficacy Scale, Functional Assessment of Cancer Therapy - General and Disabilities of the Arm, Shoulder and Hand were administered. Descriptive statistics were used to describe categorical (frequencies and percentages) and quantitative variables (mean and standard deviation). Results: The sample was composed of seventy-eight women diagnosed with breast cancer. Nine activities of daily living were affected in more than 20% of women with breast cancer. The most affected were sleep and rest and functional mobility. Conclusions: Women survivors of breast cancer showed difficulties in daily life performance and participation. The MAIA App could be useful as a new online resource in occupational therapy for the rehabilitation of breast cancer survivors.